A conodont-based revision of the Sr-87/Sr-86 seawater curve across the Permian-Triassic boundary - Dudas, Francis O.; Yuan, Dong-Xun; Shen, Shu-Zhong; Bowring, Samuel A. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Based on analyses of 565 conodonts from Meishan, Liangfengya, and Daijiagou (South China), and Abadeh (central Iran), we propose a revision of the seawater Sr-87/Sr-86 curve for the time period spanning 200 kyr prior to the Permian-Triassic boundary (PTB) to 330 kyr after the PTB. With carefully designed sample cleaning, conodonts faithfully record seawater Sr-87/Sr-86. Seawater Sr-87/Sr-86 was 0.707030 +/- 10,200 kyr prior to the PTB, rose to 0.707070 10 approximately 39 kyr prior to the PTB (at the marine extinction horizon, the top of Bed 24e at Meishan), to 0.707080 +/- 10 at the PTB, and to 0.707120 +/- 20 at 330 kyr after the PTB. The rate of change of seawater Sr-87/Sr-86 was 0.0000185/Myr from the Capitanian minimum to similar to 100 kyr before the PTB, and was 0.00020 +/- 7.5/Myr between similar to 100 kyr before and 330 kyr after the PTB. Over 6 Myr, this rate of change would result in a maximum Sr-87/Sr-86 of similar to 0.70825 at the end of the Early Triassic, compared with a model value of similar to 0.7080. The Sr data are consistent with the interpretation that the rise in marine Sr-87/Sr-86 was due primarily to an increase in the continental weathering and erosional flux, and that soil-binding vegetation was not reestablished during most of the Early Triassic. The rapid rise in seawater Sr-87/Sr-86 began at least 30 kyr prior to the marine extinction at Meishan, indicating that the terrestrial extinction preceded that in the oceans. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).